Carbon nanotube paste electrode with a bismuth film in anodic stripping voltammetry for the determination of heavy metals - Stočes, Matěj; Mikysek, Tomáš; Švancara, Ivan (Univerzita Pardubice, 2012)
In this article, a new type of metal-based non-mercury electrode based on carbon nanotubes (both multi-walled and single-walled) paste electrode is introduced and examined for electrochemical stripping analysis of selected heavy metals. All important parameters have been optimized by using Cd(II) and Pb(II) as the model ions by square-wave anodic stripping voltammetry, as well as the role of bismuth concentration. It was found that bismuth coated multi-walled carbon nanotubes paste electrode had exhibited a fine linear response at the μgper-litre concentration level of cadmium and lead.
Keywords: carbon nanotubes paste electrode; carbon nanotubes; bismuth film; electrochemical stripping analysis; heavy metals; lead; cadmium